2020
DOI: 10.21203/rs.2.23518/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high fat diet with a high C18:0/C16:0 ratio induced worse metabolic and transcriptomic profiles in C57BL/6 mice

Abstract: Background: Differential effects of individual saturated fatty acids (SFAs), particularly stearic acid (C18:0) relative to the shorter-chain SFAs have drawn an interest for more accurate nutritional guidelines. But specific biologic and pathologic functions that can be assigned to particular SFAs are very limited. The present study was designed to compare changes in metabolic and transcriptomic profiles in mice caused by high C18:0 diet and high palmitic acid (C16:0) diet. Methods: Male C57BL/6 mice were assig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The relative abundance of palmitate and stearate seems to be significant. Studies have demonstrated that either the genetic manipulation of the palmitate/stearate ratio in phospholipids (21) or the dietary alteration of the palmitate/stearate ratio (22) affect insulin resistance and body fat ratio. Thus, it seems likely that the palmitate/stearate ratio requires regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of palmitate and stearate seems to be significant. Studies have demonstrated that either the genetic manipulation of the palmitate/stearate ratio in phospholipids (21) or the dietary alteration of the palmitate/stearate ratio (22) affect insulin resistance and body fat ratio. Thus, it seems likely that the palmitate/stearate ratio requires regulation.…”
Section: Discussionmentioning
confidence: 99%
“…These tendencies were observed in all life stages, probably being a trend in T. castaneum species, when fed on maize flour. The ratio between stearic acid and palmitic acid (C18:0/C16:0) may induce worse lipid profile, insulin resistance, and alter mRNA expression, being advised to be taken into account for evaluating nutritional resources (Wang et al, 2020). In T. castaneum it was observed that this ratio was small, as palmitic acid is more abundant than stearic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Catabolism of PEA in the body gives rise to relatively inactive products (C16:0 and ethanolamine), causing no adverse effects [52]; therefore, its overall safety and efficacy profile makes it suitable for prophylactic use. However, the overconsumption of C16:0 due to nutritional imbalance and its adverse effects have also been reported in cardiometabolic and liver health [53], aggravating insulin resistance, metabolic dysregulation and dyslipidemia, thereby leading to abnormal fat distribution and deposition [54]. Indeed, a well-balanced dietary approach would be a key to keep a check on DNL.…”
Section: Palmitoylethanolamidementioning
confidence: 99%